Desenvolvimento de método de preparo de amostras de solução de nutrição enteral mediante sistema de digestão de alta pressão para posterior determinação multielementar - Anschau, Kéllen Francine (2018)
In this work two methods of sample preparation for the digestion of enteral nutrition solution (SNE) using microwave assisted digestion (MWAD) in a single reaction chamber (SRC) system and subsequent multielement determination by plasma-based techniques (ICP OES and ICP-MS) were evaluated. For H2O2, parameters such as H2O2 concentration (30, 40 and 50%), temperature of the SRC system (190, 230 and 250 ° C), volume of H2O2 (6, 8 and 10 mL) and the sample mass (ranging from 250 mg to 1500 mg) were investigated. The evaluation of the best condition was made based on the concentration of residual C and the residual acidity of the digests. The best condition for the SRC system with H2O2 was 8 mL of 50% H2O2, temperature of 250 ° C and mass of 1000 mg of SNE. In this condition, the residual C concentration obtained was 711 mg L-1 and negligible residual acidity. Subsequently, the best condition obtained with H2O2 was also applied to concentrated HNO3. Using concentrated HNO3, a residual C concentration of 123 mg L-1 and a high residual acidity (7,7 mol L-1 of HNO3) were obtained. In addition, the decomposition efficiency of the components of the SNE formulation were evaluated. For this, sodium caseinate, glucose syrup and sunflower and canola oils were digested using 8 mL of 50% H2O2. It was observed that sodium caseinate and sunflower and canola oils had the highest values of residual carbon. In addition, wet digestion of refractory organic compounds such as histidine, tryptophan, phenylalanine and linoleic acid was performed using the SRC system with 50% H2O2 and concentrated HNO3. The values of residual carbon content (RCC) obtained for these refractory organic substances were significantly lower than reported in the literature, probably due to the more drastic pressure and temperature conditions allowed by the SRC system. Finally, the determination of As, Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Mo, Na, P, Pb, Se and Zn were performed by ICP OES and ICP-MS and were not observed significant differences between the results obtained by the methods that used 50% H2O2 and concentrated HNO3. The accuracy was also evaluated with a reference material (NIST 8435 Whole Milk Powder).